Avoidance and treatment of overtraining (IAAF @-Letter for CECS Level II Coaches, 2004)
Overtraining is something that particularly affects middle- and long-distance runners, and it has been reported that at least 60% of elite distance runners have experienced it. In contrast, overtraining appears to occur much less frequently in athletes who participate in explosive sports lasting for less than two minutes, perhaps because it is more difficult during training for these events to do too much (cf. Newsholme, Leech & Duester, 1994, p. 268). The earlier the symptoms of overtraining can be identified and managed, the more rapid and successful will be a return to effective progress and the less likely will be the development of staleness (for a definition see p. 11 of this Letter). This often is not easy to do. It is unfortunate but evident that a peculiar tunnel vision frequently impairs the perception of outstanding athletes and their coaches regarding total work load management. They cannot imagine that doing too much will happen to them. Too often an individualized training plan has not provided periodic rest. Training is pushed into the realm of excess, either unknowingly or simply because of a work ethic that continually promotes the attitude that more is better, that there is no gain without pain, and that the need for rest is a sign of weakness.